The doors of Eden - Tchaikovsky, Adrian, 1972- (Orbit, 2020)
"Four years ago, two girls went looking for monsters on Bodmin Moor. Only one came back... Lee thought she'd lost Mal, but now she's miraculously returned. But what happened that day on the moors? And where has she been all this time? Mal's reappearance hasn't gone unnoticed by MI5 officers either, and Lee isn't the only one with questions. Julian Sabreur is investigating an attack on top physicist Kay Amal Khan. This leads Julian to clash with agents of an unknown power - and they may or may not be human. His only clue is grainy footage, showing a woman who supposedly died on Bodmin Moor. Dr Khan's research was theoretical; then she found cracks between our world and parallel Earths. Now these cracks are widening, revealing extraordinary creatures. And as the doors crash open, anything could come through."--